Acute and residual effects in adolescent rats resulting from exposure to the novel synthetic cannabinoids AB-PINACA and AB-FUBINACA. (June 2017) - Kevin, Richard C; Wood, Katie E; Stuart, Jordyn; Mitchell, Andrew J; Moir, Michael; Banister, Samuel D; Kassiou, Michael; McGregor, Iain S
Synthetic cannabinoids (SCs) have rapidly proliferated as recreational drugs, and may present a substantial health risk to vulnerable populations. However, information on possible effects of long-term use is sparse. This study compared acute and residual effects of the popular indazole carboxamide SC compounds AB-PINACA and AB-FUBINACA in adolescent rats with ∆ 9 -tetrahydrocannabinol (THC) and control treatments. Albino Wistar rats were injected (i.p.) with AB-PINACA or AB-FUBINACA every second day (beginning post-natal day (PND) 31), first at a low dose (0.2 mg/kg on 6 days) followed by a higher dose (1 mg/kg on a further 6 days). THC-treated rats received equivalent doses of 6 × 1 mg/kg and 6 × 5 mg/kg. During drug treatment, THC, AB-PINACA, and AB-FUBINACA decreased locomotor activity at high and low doses, increased anxiety-like behaviours and audible vocalisations, and reduced weight gain. Two weeks after dosing was completed, all cannabinoid pre-treated rats exhibited object recognition memory deficits. These were notably more severe in rats pre-treated with AB-FUBINACA. However, social interaction was reduced in the THC pre-treated group only. Six weeks post-dosing, plasma levels of cytokines interleukin (IL)-1α and IL-12 were reduced by AB-FUBINACA pre-treatment, while cerebellar endocannabinoids were reduced by THC and AB-PINACA pre-treatment. The acute effects of AB-PINACA and AB-FUBINACA were broadly similar to those of THC, suggesting that acute SC toxicity in humans may be modulated by dose factors, including inadvertent overdose and product contamination. However, some lasting residual effects of these different cannabinoid receptor agonists were subtly different, hinting at recruitment of different mechanisms of neuroadaptation.